Models of integrity art and law in post-sixties America - Kee, Joan (University of California Press, 2019)
"Models of Integrity discusses the history of the relationship between contemporary art and the law through the lens of integrity. From the late 1960s, artists engaged conspicuously with ideas, rituals, or documents of the law--an institution subject to intense moral and political scrutiny, yet whose primacy in the social infrastructure made it a widely recognized source of authority to audiences both in and out of the art world. These engagements with law were frequently undertaken in ways that signaled a recuperation of integrity compromised by the very institutions supposedly entrusted with establishing standards of just conduct. Having integrity also meant conveying to audiences the social purpose of an artwork without overstating its political impact or losing sight of how aesthetic decisions might compel audiences to see their everyday world differently"--Provided by publisher
Keywords: Geschichte 1970-2019; Law and art / United States / History / 20th century; Law and art / United States / History / 20th century / Case studies; Artists / United States / History / 20th century; Kunst; Ästhetik; Rechtssystem; Integrität -- Motiv; Politische Kunst; USA